An Assessment of Flood Shocking Tears Down: A Case Study in Bogura District - Hoque, ATM Rezaul; Angona, ANH; Ahmad, Babor (Research in Agriculture Livestock and Fisheries, 2021)
This study was conducted on two chars of Bogura district using primary data and aims at understanding of how flood affects the rural poor living in the char lands. The study revealed that floods have long-term negative implications on socio-economic status. According to survey the most affected sector was agriculture (54.03%), followed by property (28.66%) and health (19.71%), diseases as Diarrhea occurred at alarming levels (76.07%) in the study areas. In the study year food availability and roads communications were also highly affected by flood. Floods make people vulnerable; as they take away their livelihoods at the first instance and leave them with little resources to overcome from the situation. Because of floods, rural poor communities face job loss, and two-thirds of their income is reduced, which limits their capabilities of preparedness, response, and recovery to subsequent floods. People cope with the situation by bearing substantial debts and a loss of productive assets. It also examines the impacts of flood on the livelihood of the rural poor and explores their coping strategies and also observers it as a positive ingredient for fertility and soil improvement. However the present study captures both positive and negative. Res. Agric., Livest. Fish.8(1): 65-73, April 2021